Bone permeability and mechanotransduction: Some current insights into the function of the lacunar-canalicular network. (April 2022) - Murshid, Sakhr Ahmed
Highlights: The LC network mediates the passage of various components through bone tissue. LC permeability and fluid flow-shear stress are important for mechanotransduction. Alterations in LC structure may contribute to bone remodelling. Several bone-health conditions are associated with changes in LC structure and function. Abstract: Lacunar-canalicular (LC) permeability involves the passage of fluids, nutrients, oxygen, ions, and signalling molecules through bone tissue, facilitating the maintenance of bone vitality and function and responses to various physiological conditions and diseases. LC permeability and fluid flow-shear stress/drag force play important roles in mechanotransduction in bone tissue by inducing mechanical stimuli in osteocytes, modulating cellular functions, and determining bone adaptation. Alterations in LC structure may therefore influence the fluid flow pattern through the LC network, thereby affecting the ability of osteocytes to sense and translate mechanical signals and possibly contributing to bone remodelling. Several bone-health conditions are associated with changes in LC structure and function and may affect mechanotransduction and responses, although the mechanisms underlying these associations are still not fully understood. In this review, recent studies of LC networks, their formation and transfer mechanical stimuli, and changes in structure, functional permeability, and mechanotransduction that result from age, pathology, and mechanical loading are discussed. Additionally, applications of vibration and low-intensity pulsed ultrasound in bone healthcare and regeneration fields are also presented.